Regularities of elastic anisotropic strains caused by T-H-P influence on the structural transition and properties of magnetic semiconductors - Polyakov, P.I.; Kucherenko, S.S. (Functional Materials, 2004)
A generalizing analysis of experimental results on resistivity, magnetostriction, and phase transitions has been performed for magnetic semiconductors, namely, L₀.₇Ca₀.₃MnO₃ polycrystals and LaMnO₃ single crystals exposed to temperature (T), magnetic field (H), and hydrostatic pressure (P). The magneto-,baro-, and baromagnetoresis-tive effects have been revealed, where their maxima temperatures, Tpp, have been found to be constant and to coincide with the metal-semiconductor structural phase transition (PT) temperature, Tms. The "cooling" and "heating" effects of the magnetic field and pressure have been established, thus enabling to validate the regularities of Tms(H), Tms(P), and Hg(T) variations. The correspondence between T-H-P effect (5.1 К ~ 2.42 kOe ~ 1 kbar) on the resistivity properties and T-H effect (5.2 К-2.5 kOe) on the magnetostriction properties of the magnetic semiconductors has been estimated. The sign alternation has been revealed in variations of properties and effects as well as regularities of competing influence of thermo-, baro-, and magneto-elastic anisotropically straining (EAS) stresses. The positions of critical lines Tms(H), Tms(P), Hg(T) and points Tx, Px, PPX, Px', Tpp = Tms, T& have been defined, their correspondences in resistivity and magnetostriction behaviors has been established. Basing on the variety of critical lines and points, the correspondence and sign alternation of T-H-P influence through the mechanism of EAS stresses have been substantiated.